2022
DOI: 10.3390/land11030448
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Private and Public Pro-Environmental Behaviors in Rural Tourism Contexts Using SEM and fsQCA: The Role of Destination Image and Relationship Quality

Abstract: The importance of pro-environmental behavior in tourism has been established, but explaining its sub-dimensions, especially in the private and public dimensions, is under-researched. Existing literature on tourism research mainly uses SEM to analyze tourist pro-environmental behavior, while fsQCA is scarcely implemented. In this study, SEM is applied to reveal the links among destination image, relationship quality, and pro-environmental behavior, while fsQCA is utilized to investigate configurations predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 146 publications
(243 reference statements)
0
23
0
Order By: Relevance
“…Relational constructs included in the conceptual framework of the present research were verified to play substantial mediating roles. Despite the evidence in marketing research and tourism research [ 55 , 59 , 60 ], limited studies have applied environmental identification and environmental commitment to measure relationship quality and predict environmental citizenship behavior [ 9 , 27 ]. By taking both environmental identification and environmental commitment into account, our research demonstrated how residents’ identification with the destination, and commitment to environment conservation, promote residents to adopt citizenship behavior for maintaining environmental sustainability in rural destinations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Relational constructs included in the conceptual framework of the present research were verified to play substantial mediating roles. Despite the evidence in marketing research and tourism research [ 55 , 59 , 60 ], limited studies have applied environmental identification and environmental commitment to measure relationship quality and predict environmental citizenship behavior [ 9 , 27 ]. By taking both environmental identification and environmental commitment into account, our research demonstrated how residents’ identification with the destination, and commitment to environment conservation, promote residents to adopt citizenship behavior for maintaining environmental sustainability in rural destinations.…”
Section: Discussionmentioning
confidence: 99%
“…As relationship quality theory proposes, building relationships is centered on identifying and addressing the needs of people [ 54 ]. From this point of view, one of the effective strategies for encouraging people’s positive behavior is to improve relationship quality [ 55 , 56 ]. In tourism, a healthy environment provides residents with benefits in diverse ways, such as increasing their satisfaction toward life and improving their physical and mental well-being [ 57 , 58 ].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to providing the destinations with financial advantages, the increase in tourist arrivals and activities also raises environmental concerns [8,9]. Tourists are key stakeholders of destinations [10,11]. Their undesirable behaviors negatively affect sustainable development [12], such as littering, graffiti, and overcrowding [10,13,14].…”
Section: Introductionmentioning
confidence: 99%